'The Nation is Coming to Life': Law, Sovereignty, and Belonging in Ngarrindjeri Photography of the Mid-Twentieth Century. Issue 3 (3rd July 2018) - Hughes, Karen; Trevorrow, Ellen
Abstract : From the moment small consumer cameras became available in Australia in the early twentieth century, Ngarrindjeri people embraced photography as a means to record their history, and represent their families, aesthetic traditions, and worldviews against the perilous times of attempted assimilation by the state, including the rampant forced removal of Aboriginal children that came to be known as the Stolen Generations. In analysing a collection of rare historical photographs from this period, taken by Ngarrindjeri photographers and retained in Ngarrindjeri families, we bring the perspectives of contemporary Ngarrindjeri Elders to bear. Significantly, the photographs can be observed to operate both as a rich counter archive to colonial representation and settler memory, and as esteemed cultural objects capable of drawing the weight of the ancestral past into the present moment, thereby tangibly enlivening cultural and spiritual connections generationally today. Our exploration in this article provides new theoretical perspectives and fresh historical insight into the ways in which photography has been substantially deployed by an Australian Aboriginal nation as a subtle and potent tool to assert self-determination, document survivance, and enact visual sovereignty.